Ecosystems of youth leadership development - Swed, Trisha A. (Emerald points., 2025)
Ecosystems of Youth Leadership Development: Pathways to New Programs introduces new insights into youth leadership development, where the voices of youth who have been disaffected by previous programs are brought to the forefront. This is opposed to past studies where research is often grounded in understanding only the positive experiences of youth involved in leadership development. These past studies often only implement an adult-centric point of view when determining the value of youth experiences. Serving as a guide for educators, practitioners, and communities, the book provides examples, research, and tools for analyzing existing programs and creating new programs. Readers can use this book to think about constructive ways to meaningfully connect youth to their communities and create sustainable, long-lasting relationships. Throughout these chapters, practitioners, educators, and community leaders can find studies, student testimonies, examples, and activities they can engage with to further explore the inner workings of youth leadership development programs.